An Abundant Food System - Libby, Russell (Maine Policy Review, 2011)
Russell Libby imagines what an abundant food system would look like for Maine and what it would take to get there. His recommendations include expanding the production and financing base, encouraging year-round production systems, building up mid-sized markets, and integrating farms into the ecosystem
Keywords: Maine; food system; local foods; organic farming